2010
DOI: 10.4314/ijbcs.v4i2.58138
|View full text |Cite
|
Sign up to set email alerts
|

Effet répulsif du kaolin contre les populations d'<i>Aphis craccivora</i> (<i>Homoptera: Aphididae</i>) sur le niébé (<i>Vigna unguiculata</i>)

Abstract: RESUMEFace aux nombreux dégâts causés par le puceron du niébé, Aphis craccivora, on a été amené à établir des programmes de protection phytosanitaire basés essentiellement sur l'utilisation intensive des produits chimiques. Cette utilisation intensive d'insecticides chimiques conduit au développement du phénomène de résistance et provoque un déséquilibre de l'écosystème parce que ces insecticides chimiques tuent également les organismes utiles et s'accumulent dans le sol, l'air, l'eau et la chaîne alimentaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…En effet, les attaques de ces insectes et parasites conduisent souvent simultanément à la réduction de la croissance ou à des pertes des plantes atteintes (Alavo, 2010;N'Gbesso et al, 2013 ;Yoka et al, 2014). Ces ravageurs infligent des dégâts très importants si aucune mesure de protection n'est mise en oeuvre (Dugjé et al, 2009 ;Tonessia et al, 2009).…”
unclassified
“…En effet, les attaques de ces insectes et parasites conduisent souvent simultanément à la réduction de la croissance ou à des pertes des plantes atteintes (Alavo, 2010;N'Gbesso et al, 2013 ;Yoka et al, 2014). Ces ravageurs infligent des dégâts très importants si aucune mesure de protection n'est mise en oeuvre (Dugjé et al, 2009 ;Tonessia et al, 2009).…”
unclassified
“…It was therefore concluded that 5 % kaolin powder and adequate application method that provides a full and continuous coverage of the plants with kaolin particle film should be used [9]. Nevertheless, one week interval application of this concentration does not completely suppress populations of A. craccivora and A. gossypii [9,10]. The present work has revealed that even more frequent kaolin applications do not improve the product efficacy against L. erysimi.…”
Section: Discussionmentioning
confidence: 61%
“…The effects of kaolin against aphid species such as Aphis craccivora [10] and Aphis gossypii [9] have been investigated. As in the present study, these works have showed that the solution containing 5 % kaolin powder has significantly reduced aphids' population density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations